METHODOLOGY FOR DETERMINING INDICATORS OF GENERAL AND SPECIFIC PHYSICAL PREPARATION OF HIGHLY SKILLED BELT WRESTLERS - Toychiev Tahirjon Sahodillaevich (Research Focus International Scientific Journal, 2023)
This article presents the tests obtained on the basis of a set of special exercises, in addition to which a complex methodology was developed for the development and control of high-skilled belt wrestlers by identifying the general, specific physical training process.